Progeria: A new kind of Laminopathy Report of the First European Symposium on Progeria and creation of EURO-Progeria, a European Consortium on Progeria and related disorders - (:unkn) unknown (My University, 2004)
Progeria is a rare, genetically determined condition characterized by accelerated aging in children. Its name is derived from Greek (Geron) and means "prematurely old". The classic type is the Hutchinson-Gilford Progeria Syndrome (HGPS), which was first described in England in 1886 by Dr. Jonathan Hutchinson (1) and again in 1904 by Dr. Hastings Gilford (2). Since then and up to now, very little advancement toward the understanding of this devastating disorder has been accomplished. In early 2003 a French group succeeded in identifying point mutations in the LMNA gene, encoding A-type lamins, as the main cause of this disorder. These results were concomitantly confirmed by an American group, who identified mutations in LMNA, working on a large cohort of patients (3,4). HGPS is thus the most severe disorder added to the expanding list of "laminopathies", diseases caused by mutations in the LMNA gene encoding A-type lamins. To date, up to ten disorders are associated with mutations in LMNA. These disorders are diverse, both in their symptomatology and pattern of inheritance (see below and table 1). Due to the extremely low prevalence of progeria and the putative functional links between progeria and other premature aging disorders, setting-up a network about these disorders has become an absolute necessity. A reunion of families with a child affected with progeria, gathered within the European Progeria Family Circle, was held from September 25th to 29th 2003 in Magdeburg, Germany. In parallel to this event, a scientific symposium centered on clinical and molecular update of HGPS and related syndromes was organised. Several international experts, including clinical and molecular geneticists, cell biologists involved in the field of laminopathies, as well as paediatricians and other physicians with clinical experience in diagnosis, treatment and research on progeria and progeria-like syndromes presented their experience as well as their research projects and yet unpublished results. The main discussed topics as well as the developing research fields on progeria and related premature ageing disorders will be presented here.
Keywords: Aging; Lamins; LMNA; Nuclear envelope; Progeria